Contributions of Fritz Leisch to Vignettes and Reproducible Research - Robert Gentleman; Anthony Rossini; Vincent Carey (Austrian Journal of Statistics)
In this paper we review the contributions of Dr. Fritz Leisch to the areas of reproducible research and software documentation. We first review three emergent use cases for these contributions and then describe the computational tools and methods needed to support them. We then discuss some of the risks that exist for each of the use cases and consider developments that might help to mitigate those risks. And we end by considering how they may evolve in the coming years.